Stochastic Simulation to Determine the Present Net Value and Uncertainty Costin a Wind Power Plant (2019)
This document presents a proposal for stochastic simulation to determine the investment uncertainties and the uncertainty cost of operation for a wind power plant. Taking as a study object a hypothetical wind plant in Cabo de la Vela, in La Guajira, Colombia, with the same characteristics as the current  Jepirachi plant of EPM, where the probability density function of the net present value of the project is found, and the probability of project profitability. Additionally, the uncertainty cost for the operation of the plant is determined depending on the different monthly scenarios of the primary energy (wind speed). This cost approximates a quadratic function that serves as a cost element in the problem of economic dispatch considering renewables. Finally, the results obtained and future developments are discussed